دور المجلس الشعبي البلدي في تسيير المرافق التربوية :دراسة مقارنة بين بلدية قلتة سيدي سعد و بلدية تاويالة بولاية الأغواط - صافني صافية; قرارمة آسيا; جوبر محمد (جامعة عمار ثليجي -الأغواط, 2022)
The municipality is the basic regional group of the state in the Algerian administrative organization, and it the basis for the embodiment of any local development plan. Ln support of educational facilities in order to improve the capabilities of the younger generation, therefore, our study aims to identify one of the important topics represented in the role of the Municipal people Council (the municipality) in the management of educational facilities (primary schools) in the municipality of Galtat Sidi saad the municipality of Taouiala in the wiles of Laghouat ,by adopting on comparative study that combines the two municipalities ,and the study concluded in the end that study concluded in the end that there is a strong relationship between the municipality and the school through that it controls all aspects related to it except for the administrative aspect of the Ministry of National Education. keywords : Municipal people council ,educational facilities , Jabir Bel Abbas primary school in the municipality of Galtat Sidi saad ,Jalakh Mohamed primary school in the municipality of Taouiala